Effects of Endotracheal Tube with Adhesive Superficial Laryngeal Electrodes for Intraoperative Nerve Monitoring on Laryngopharyngeal Complications during Thyroidectomy - Jiae Moon; Jin Kyong Kim; Hye Jung Shin; Jooeun Park; Na Young Kim; Kee-Hyun Nam (Biomedicines, 2023)
The endotracheal tube (ETT) with laryngeal adhesive electrodes for intraoperative neural monitoring (IONM) may be related to laryngopharyngeal complications, such as postoperative sore throat (POST), hoarseness, and coughing. We aimed to evaluate the effects of the ETT with laryngeal adhesive electrodes for IONM on the occurrence of laryngopharyngeal complications during thyroidectomy. In this retrospective study, we included 176 patients who underwent thyroidectomy for thyroid cancer between September 2020 and February 2021. The patients were categorized into control (n = 108) and IONM (n = 68) groups. Patients in the IONM group were intubated with the ETT with surface electrodes. Characteristics of the patients and surgery, perioperative variables, and laryngopharyngeal complications, including POST, hoarseness, and cough, were evaluated. The severity and incidence of POST were comparable between the two groups on postoperative days 0, 1, and 2 (p = 0.103, 0.386, and 0.056, respectively). Furthermore, no significant differences were observed in the occurrence of postoperative hoarseness and cough between the groups. The ETT with laryngeal adhesive electrodes for IONM during thyroidectomy did not affect the incidence and severity of postoperative laryngopharyngeal complications, including POST, hoarseness, and cough. Further prospective, double-blinded, randomized clinical trials are required to gain a clearer understanding.